The Promise and Perils of Inter-Religious Education - Boys, Mary C. (Toronto journal of theology, 2010)
History reveals that inter-religious dialogue does not come naturally. Yet it is so crucial to creating a peaceful world. If inter-religious dialogue is to flourish, then participants must be educated for it. At its best, inter-religious education involves an experience of "thin places" that arises from exploring ultimate truths in the presence of the religious other. It also requires the development of "thick religiosity," that is, knowledge of sacred texts and the play of interpretations; commitment to the communal and transformative character of religion; awareness of the historical and cultural contexts in which the tradition originated and developed; sensitivity to the rich panoply of folk traditions, rituals, art, music, and devotions in which religion has been celebrated and communicated; and attentiveness to the contemplative dimension of life. Thick religiosity, in other words, is a "textured particularism" that forms persons in a religious identity that is simultaneously rooted and adaptive, assured and ambiguous—that is, an identity strong and supple enough to contribute to a responsible pluralism. Conversation between religious others with a thick religiosity is the threshold to thin places.